Contribution to the study of the durability of rubberized concrete in aggressive environments - Kechkar, Chiraz; Belachia, Mouloud; Cherait, Yacine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Today, much of the world`s waste, in particular used tires, is accumulating as a potential source of major environmental and economic problems. In order to better preserve the environment, and in the face of changes in the legislation in force, many recovery actions have been carried out especially in the field of building materials.
Keywords: concrete; rubberized concrete; durability; wastes; aggressive environments; beton; beton gumowo-asfaltowy; trwałość; odpady; środowisko agresywne